2020
DOI: 10.1038/s41467-020-16651-5
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of Mediator 12 and 13 as conditional positive gene regulators in Arabidopsis

Abstract: Mediator 12 (MED12) and MED13 are components of the Mediator multi-protein complex, that facilitates the initial steps of gene transcription. Here, in an Arabidopsis mutant screen, we identify MED12 and MED13 as positive gene regulators, both of which contribute broadly to morc1 de-repressed gene expression. Both MED12 and MED13 are preferentially required for the expression of genes depleted in active chromatin marks, a chromatin signature shared with morc1 reactivated loci. We further discover that MED12 ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 71 publications
1
29
0
Order By: Relevance
“…Therefore, it is possible that the termination of Pol II elongation at − 60 nt is caused by a unique chromatin status at the tRNA gene promoter. To test this scenario, we analyzed published data of MNase-seq [ 61 ], ChIP-seq (H3K4me3, H3K36me3, H3K27me3, H3K9me2) [ 62 ], and the CG, CHG, and CHH DNA methylation level to check the chromatin status at the two tRNA loci showed in Fig. 4 , including nucleosome positioning, histone modification, and DNA methylation (Additional file 1 , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is possible that the termination of Pol II elongation at − 60 nt is caused by a unique chromatin status at the tRNA gene promoter. To test this scenario, we analyzed published data of MNase-seq [ 61 ], ChIP-seq (H3K4me3, H3K36me3, H3K27me3, H3K9me2) [ 62 ], and the CG, CHG, and CHH DNA methylation level to check the chromatin status at the two tRNA loci showed in Fig. 4 , including nucleosome positioning, histone modification, and DNA methylation (Additional file 1 , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of loss-of-function mutants in Mediator subunits revealed that the plant Mediator complex regulates transcription in a specific manner. Whereas the Mediator subunits might not be all required for general gene transcription, they are implicated in the control of various pathways (Kidd et al, 2009;Elfving et al, 2011;Hemsley et al, 2014;Ruiz-Aguilar et al, 2020;Liu et al, 2020). So far, Mediator subunits have been reported to play roles in organ and tissue development, hormone signaling, flowering transition, immune response, and abiotic stresses (Kidd et al, 2009;Wang et al, 2011;Bendía-Monreal and Gillmor, 2016;Crawford et al, 2020;Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…S15 ). To further test the hypothesis that up-regulation of ATXR6 expression may be sufficient to suppress the atxr5/6 phenotype, we crossed atxr5/6 (W) with mediator12 ( med12 ) ( 23 ), which has pleiotropic effects on gene expression. Loss of MEDIATOR12 increased ATXR6 expression and suppressed the TE up-regulation and extra DNA phenotypes of atxr5/6 (W) ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%